2005
DOI: 10.1159/000086688
|View full text |Cite
|
Sign up to set email alerts
|

Does a Carbon Ion-Implanted Surface Reduce the Restenosis Rate of Coronary Stents?

Abstract: Background: Neointimal hyperplasia and resulting restenosis limit the long-term success of coronary stenting. Heavy metal ions induce an inflammatory and allergic reaction, and result in in-stent restenosis. However, a carbon ion-implanted surface might prevent heavy metal ions from diffusing into surrounding tissue. Methods: 140 lesions in 140 patients with coronary lesions underwent implantation of carbon-implanted surface stents (Arthosinert stent group, n = 70) or control stents (Arthos stent gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…The studies included in this systematic review were published in nine articles between 2005 and 2020. Seven articles were randomised controlled trials [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ], and two were prospective study designs [ 28 , 29 ]. A total of 1049 patients who had undergone PCI and who were stented were included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies included in this systematic review were published in nine articles between 2005 and 2020. Seven articles were randomised controlled trials [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ], and two were prospective study designs [ 28 , 29 ]. A total of 1049 patients who had undergone PCI and who were stented were included.…”
Section: Resultsmentioning
confidence: 99%
“…In patients presenting systemic evidence of inflammation as measured by an elevated hs-CRP level at baseline and follow-up, the administration of oral anti-inflammatory therapy post-stenting dramatically reduces the rate of restenosis, as reported by Gaztanaga J [ 21 ], Rosa W C [ 22 ], and Yao W [ 23 ]. Meanwhile, Jung J H [ 24 ], Kochiadakis G E [ 25 ], and Wang J [ 26 ] reported that the profound impact of DES on restenosis prevention reflects both its properties as an anti-proliferative as well as an anti-inflammatory agent. Such studies underscore the important role of anti-inflammation in the attendant risks of restenosis or thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations